Catholics and violence in the Nineteenth-Century global world - Bouwers, Eveline G. (Routledge studies in modern history, 2024)
IntroductionViolence and the Negotiation of Difference: Nineteenth-Century Catholic Encounters with the Religious and Secular OtherEveline G. BouwersPart 1: Rejecting Secularization Chapter 1Religion and Violence during the French Revolutionary and Napoleonic Wars: Between Tradition and ModernityPhilip DwyerChapter 2"To Be Consumed in Suffering for His Love": Violence, Religion, and Counterrevolution in Restoration SpainMary VincentChapter 3Anti-Liberal Violence in Belgium: Catholics in Defiance of State Legislation, 1857-1884Eveline G. BouwersPart 2: Contending Clericalism Chapter 4Collective Violence and the Religious Politicization of Peasants on the Habsburg Periphery: Rabatz and Antisemitic Riots in West Galicia, 1846-1898 Tim BuchenChapter 5Between the Soldiers of Pius IX and the Sons of Saint Felicitas: Catholic Pluralism and Religionero Violence in Michoacán, Mexico, 1873-1877Brian A. StaufferChapter 6Religion and Violence in Nineteenth-Century Argentina: Teachings from the 1875 Anticlerical RiotsRoberto Di StefanoPart 3: Resisting Religious Pluralization Chapter 7From Violent Acts to Violent Hatred: French Catholic Responses to the Damascus and Dreyfus AffairsJulie KalmanChapter 8The Trillick Railway Outrage: The Politics of Atrocity in Post-Famine UlsterSean FarrellChapter 9Catholicism and Violence in Korea: Two Case Studies from the Chosŏn DynastyFranklin RauschPart 4: Imposing a Catholic Order Chapter 10Violence in Circulation? Missionaries, Local Population, and Colonial Politics during the German War on the East African Coast, 1888-1889Richard HölzlChapter 11Catholic Missionaries in Central Africa: Violence and the Creation of Religious Statehood in South Eastern Congo during the Partition Era, 1867-1914Reuben A. LoffmanChapter 12"The Children Grow Up Without Discipline": Religion, Childhood, and Violence in Colonial New Guinea around 1900 Katharina StornigPart 5: Opposing Catholic Invasion Chapter 13Pageantry in the Shadow of Violence: Celebrating Fête-Dieu in Mid-Nineteenth-Century MontrealDan HornerChapter 14The Popery Panic: Nativism, Anti-Catholicism, and Violence in Antebellum America Cassandra L. YacovazziChapter 15Occasional Martyrs: Catholic Life in Nineteenth-Century China between Coexistence and SubjugationLars Peter LaamannPart 6: ConclusionsChapter 16Parameters of Religion-Related Violence in Modern History Eveline G. Bouwers